EXPRESSION OF SEASONS IN FRENCH PROVERBS AND SAYINGS AND THEIR EQUIVALENTS IN UZBEK (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article consists of studying French proverbs and sayings, giving examples of seasons and nature, and finding their Uzbek equivalents. We can also compare their similar and different aspects, change the meaning during the translation process, or see changes in the examples. In this article you can get acquainted with the history, sociocultural and agricultural examples of French and Uzbek proverbs and sayings.